Shooting to Kill The Ethics of Police and Military Use of Lethal Force - Doyle, Hannah (Oxford University Press, 2016)
Terrorism, the use of military force in Afghanistan, Iraq and Syria, and the fatal police shootings of unarmed persons have all contributed to renewed interest in the ethics of police and military use of lethal force and its moral justification. In this book, philosopher Seumas Miller analyzes the various moral justifications and moral responsibilities involved in the use of lethal force by police and military combatants, relying on a distinctive normative teleological account of institutional roles. His conception constitutes a novel alternative to prevailing reductive individualist and collectivist accounts. As Miller argues, police and military uses of lethal force are morally justified in part by recourse to fundamental natural moral rights and obligations, especially the right to personal self-defense and the moral obligation to defend the lives of innocent others. Yet the moral justification for police and military use of lethal force is to some extent role-specific. Both police officers and military combatants evidently have an institutionally-based moral duty to put themselves in harm's way to protect others. Under some circumstances, however, police have an institutionally based moral duty to use lethal force to uphold the law; and military combatants have an institutionally based moral duty to use lethal force to win wars. Two key notions in play are joint action and the natural right to self-defense. Miller uses a relational individualist theory of joint actions to construct the notion of multi-layered structures of joint action in order to explicate organizational action. He also provides a novel theory of justifiable killing in self-defense. Over the course of his book, Miller covers a variety of urgent topics, such as police shootings of armed offenders, police shooting of suicide-bombers, targeted killing, autonomous weapons, humanitarian armed intervention, and civilian immunity.